Analysis of the Impact and Effectiveness of School Operational Assistance Fund Management in Tanjungbalai City - Syahri Ramadhan; Reni Ria Armayani Hasibuan; Hendra Harmain (Yayasan Riset dan Pengembangan Intelektual, 2023)
The aim of this research is to analyze the impact and effectiveness of managing school operational assistance funds at State Elementary School 130004 Tanjungbalai City in 2023. The research method applied is a qualitative descriptive method with the research subject being State Elementary School 130004 Tanjungbalai City. Data collection techniques are interviews, observation and documentation. The results of the research show that the level of effectiveness in managing school operational assistance funds at Tanjungbalai 130004 Public Elementary School in 2023 reaches 100%, indicating that the management of these funds has been running very well and optimally. The positive and negative impacts of school operational assistance funds are that on the one hand, school operational assistance funds have helped lower middle class communities meet their educational needs, as well as improving the facilities and quality of education in schools. On the other hand, some people do not care about student development because they rely too much on school operational assistance funds. School renovations, toilet repairs, purchasing learning equipment, and providing textbooks and stationery are examples of significant contributions to school operational assistance funds. However, direct observation revealed a discrepancy between the interview results and actual conditions. Although physical facilities and educational resources have been improved, there are still inadequate rooms, such as cracked toilets and damaged classrooms. Nevertheless, the role of school operational assistance funds in improving student welfare remains the main focus in efforts to improve the quality of education.